Customer satisfaction and retailer image as drivers of customer loyalty: evidences from polish supermarkets - Бєсок, Г.; Biesok, Grzegorz (Видавництво Львівської політехніки, 2020)
Наведено результати досліджень лояльності клієнтів на ринку роздрібної торгівлі. Вивчається ступінь впливу задоволеності споживачів та іміджу підприємств роздрібної торгівлі на лояльність клієнтів. Використано первинні дані опитування, багатоелементні шкали та моделювання структурних рівнянь (SEM). Концептуальна модель, що використовується у дослідженні, поєднує 3 приховані змінні: імідж продавця, задоволеність клієнтів та лояльність клієнтів. Прихованим змінним відповідає набір проявлених змінних, що були отримані під час опитування. Опитували клієнтів супермаркетів на півдні Польщі. Анкети були поширені за допомогою методу снігової кулі. Загалом у вибірку входили 328 респонденти. Моделювання структурного рівняння підтвердило всі взаємозв’язки в моделі із високим рівнем значущості (p <= 0,001). Отже, модель є прийнятною. Дослідження показало, що імідж підприємств роздрібної торгівлі та задоволеність споживачів значно впливають на лояльність клієнтів. Важливим висновком є те, що задоволеність клієнтів має вдвічі більший вплив на лояльність, ніж імідж продавця. Отже, роздрібні торгівці повинні зосередити увагу на підвищенні задоволеності клієнтів, оскільки це головний чинник їх лояльності.

The paper presents results of research on customer loyalty drivers on retail market. It verifies the degree of impact of customer satisfaction and retailer image on customer loyalty. The paper uses primary survey data, multi-item scales and structural equations modelling (SEM). The conceptual model used in the study combines 3 latent variables: retailer image, customer satisfaction and customer loyalty. Latent variables were equipped with a set of manifest variables, and they were measured in a survey. The paper assumes the following hypotheses: H1: there is a strong positive impact of retailer image on customer loyalty; H2: there is a strong positive impact of customer satisfaction on customer loyalty; H3: retailer image has a certain influence on customer satisfaction, as well. The survey was focused on supermarkets from southern Poland and their clients. The questionnaires were distributed using snowballing method. In total the sample included 328 respondents. A given table provides the results of the survey with the elements and structure of the sample. Reliability of the measurement model was evaluated with reliability coefficients: Cronbach’s α and McDonald's ω. All blocks of manifest variables showed sufficient internal consistency (α and ω >0.7) so they could be used to determine the model. Structural equation modelling confirmed all relationships in the model at a high significance level (p <= 0.001). Additionally the model fit reached sufficient level. In the result the study showed that retailer image and customer satisfaction have important influence on customer loyalty. An important finding is that customer satisfaction has two times bigger impact on loyalty than retailer image. This led into conclusion that retailers should focus on building customer satisfaction, as it is the main drive of loyalty. The conclusion is made about the understanding of customer needs and expectations and meeting them should be a priority for managers, because it translates into customer affection and adequate profitability in the long term. The author highlights, that future research should concentrate on the different types of loyalty and theirs drivers, because there relation are not sufficiently explained in the literature. In author’s opinion, the relation between brand loyalty and loyalty to the retailer is also an interesting field of research. In general, the article emphasizes the importance of scientific research of the relationships of buyers and retailers, that provide those services is very important in both theoretical and practical terms. This field of activity occupies one of the main areas of any country economy.
Задоволеність споживача та імідж підприємств роздрібної торгівлі як чинники лояльності споживача: досвід польських супермаркетів
Keywords: дослідження споживачів; задоволеність споживачів; лояльність клієнтів; супермаркети; роздріб; consumer research; customer satisfaction; customer loyalty; supermarkets; retail; M31